Prospective memory and ageing paradox with event-based tasks: A study of young, young-old, and old-old participants. Issue 5 (May 2013) - Kvavilashvili, Lia; Cockburn, Janet; Kornbrot, Diana E.
Research on ageing and prospective memory—remembering to do something in the future—has resulted in paradoxical findings, whereby older adults are often impaired in the laboratory but perform significantly better than younger adults in naturalistic settings. Nevertheless, there are very few studies that have examined prospective memory both in and outside the laboratory using the same sample of young and old participants. Moreover, most naturalistic studies have used time-based tasks, and it is unclear whether the prospective memory and ageing paradox extends to event-based tasks. In this study, 72 young (18–30 years), 79 young-old (61–70 years), and 72 old-old (71–80 years) participants completed several event-based tasks in and outside the laboratory. Results showed that the ageing paradox does exist for event-based tasks but manifests itself differently from that in time-based tasks. Thus, younger adults outperformed old-old participants in two laboratory event-based tasks, but there were no age effects for a naturalistic task completed at home (remembering to write the date and time in the upper left corner of a questionnaire). The young and old-old also did not differ in remembering to retrieve a wristwatch from a pocket at the end of the laboratory session. This indicates that the paradox may be due to differences in ongoing task demands in the lab and everyday life, rather than the location per se. The findings call for a concentrated effort towards a theory of cognitive ageing that identifies the variables that do, or do not, account for this paradox.